(untitled) (Szociológiai Szemle, 2024)
In this analysis we assess the effects of different social characteristics of individuals on the propensity to marriage taking into account the joint educational distribution of spouses. In line with the theoretical hypotheses and the findings of previous research, we have found a tendency for individuals with similar amount of education to marry one another. Persons with compulsory schooling and with university degree are the most likely to marry homogamously. The odds of marrying persons with equal or higher education is greater as individuals are getting older. However, the magnitude of the variable on time out of school becomes smaller on the higher levels of educational hierarchy, especially on university level. This finding refers to the low-cost marriage market function of universities, the fact that these institutions collect students whose future socio-economic outlooks are very homogeneous. Parental education has a consistent effect on marital behaviour. Well-educated individuals who possess more amount of inherited educational capital appear to gain more advantage in marriage market compared to their counterparts with less advantageous background. While for poor-educated persons the lack of parental resources further decreases the likelihood of a good match. As for the historical trends are concerned, the likelihood of marriage with poor-educated candidates has declined the most; and in the case of better-educated potential spouses the marriage propensity has even increased, or at least has not decreased to a large extent. This tendency indicates a changing economic context of marriage. Wives’ potential occupational success - which is predictable quite well by their educational attainment - may provide the family with a highly adaptive strategy. Women’s economic resources may reduce the risk of the collapse of families’ financial situation, and it provides a device of helping to maintain living conditions over family’s life-cycle. In addition, wives’ career resources may have positive effect on their husbands’ future labour market success. In sum, modern long-run partnerships are based on whether partners can make a similar valuable contributions to the marriage in order to maintain or increase the total wealth and success of the family.